2021
DOI: 10.1016/j.powtec.2020.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the flowability of powder mixtures from their single components properties through the multi-component population-dependent granular bond number; extension to ground powder mixtures

Abstract: The granular Bond number, defined as the ratio between interparticle attractive forces and particle's weight, can be computed to predict the flow behavior of powders. Previous studies used this dimensionless number to predict the flowability of various pharmaceutical or ceramic powders, exhibiting polydispersed particle size distributions. In this paper, we employ a multi-component population-dependent granular Bond number in order to apply this model to powder mixtures. Some binary and ternary mixtures are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
0
0
Order By: Relevance
“…2 show that the particles shape does not change drastically before and after grinding. This was already evidenced in a previous paper where the authors shown that the particle size is actually the most important parameter governing the flowability of this specific powder along the grinding process [24].…”
Section: Parameters Linked To the Energy Provided To The Vesselsupporting
confidence: 63%
“…2 show that the particles shape does not change drastically before and after grinding. This was already evidenced in a previous paper where the authors shown that the particle size is actually the most important parameter governing the flowability of this specific powder along the grinding process [24].…”
Section: Parameters Linked To the Energy Provided To The Vesselsupporting
confidence: 63%
“…Two trends for the Bond numbers are shown in the figure, which indicates that the surface energies of the particles cause the difference rather than the domain for the geometry of the powders. Therefore, a Bond number can represent particle adhesion at a specific size, which will be helpful for assessing powder cohesiveness at a bulk level and is also applied by other researchers [22,23]. The results in Fig.…”
Section: Figure 12mentioning
confidence: 98%